A novel serpin with antithrombin-like activity in Branchiostoma japonicum: implications for the presence of a primitive coagulation system. - Yeqing Chao (Public Library of Science (PLoS), 2012)
Serine protease inhibitors, or serpins, are a group of widely distributed proteins with similar structures that use conformational change to inhibit proteases. Antithrombin (AT) is a member of the serine protease inhibitor superfamily and a major coagulation inhibitor in all vertebrates, but its evolutionary origin remains elusive. In this study we isolated for the first time a cDNA encoding an antithrombin homolog, BjATl, from the protochordate Branchiostoma japonicum. The deduced protein BjATl consisted of 338 amino acids sharing 36.7% to 41.1% identity to known vertebrate ATs. BjATl contains a potential N-linked glycosylation site, two potential heparin binding sites and the reactive center loop with the absolutely conserved sequence Gly-Arg-Ser; all of these are features characteristic of ATs. All three phylogenetic trees constructed using Neighbor-Joining, Maximum-Likelihood and Bayesian-Inference methods also placed BjATl together with ATs. Moreover, BjATl expressed in yeast cells was able to inhibit bovine thrombin activity by forming a SDS-stable BjATl-thrombin complex. It also displays a concentration-dependent inhibition of thrombin that is accelerated by heparin. Furthermore, BjATl was predominantly expressed in the hepatic caecum and hind-gut, agreeing with the expression pattern of AT in mammalian species. All these data clearly demonstrate that BjATl is an ortholog of vertebrate ATs, suggesting that a primitive coagulation system emerged in the protochordate.